Genotypic analysis of measles viruses in southern Africa: implications for regional and global elimination of measles - Smit, Sheilagh Brigitte (My University, 2013)
Measles is a vaccine-preventable disease. Implementation of global vaccination programmes has resulted in a dramatic decrease in measles-related deaths, from 2.6 million in 1980 to 164 000 in 2008. To support the global measles elimination goal, laboratories provide case-based surveillance which includes both serological diagnosis and viral characterisation using molecular platforms. In this study, conventional hemi-nested amplification methods were developed to detect the nucleoprotein- and haemagglutinin-genes of measles virus, in specimens collected for rashsurveillance programmes in Africa. Viral characterisation involved amplicon sequencing and phylogenetic analyses of 1402 PCR-positive specimens (2655 specimens tested, 52.8% PCR-positive) with sequence submission to global databases. Only imported strains of genotypes B2, B3, D2, D4 and D8, have been detected in South Africa since 2002, demonstrating the successful interruption of transmission of endemic strains. Genotypic analyses of specimens from African countries provided information relating to strain origins, as well as temporal and spatial data relevant to the molecular epidemiology of measles in Southern Africa.
Keywords: Measles Virus